2018
DOI: 10.1111/acer.13756
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Developmental Framework to the Self‐Regulatory Difficulties of Young Children with Prenatal Alcohol Exposure: A Review

Abstract: Prenatal alcohol exposure (PAE) can be associated with significant difficulties in self-regulatory abilities. As such, interventions have been developed that focus on improving varying aspects of self-regulation for this population. The application of a multilevel theoretical framework that describes the development of self-regulation during early childhood could further advance the field. First, this framework could assist in elucidating mechanisms in the trajectories of early adjustment problems in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 99 publications
(146 reference statements)
1
4
0
Order By: Relevance
“…Atypical sensory processing behaviors and internalizing problems were commonly described by caregivers in this study and, likewise, have been reported in the literature among infants/toddlers with PAE [ 15 , 55 , 56 , 57 ]. Concerns related to selfregulation, such as difficulty soothing or sleep complaints, were also consistent with selfregulatory difficulties seen in this population [ 58 ].…”
Section: Discussionsupporting
confidence: 55%
“…Atypical sensory processing behaviors and internalizing problems were commonly described by caregivers in this study and, likewise, have been reported in the literature among infants/toddlers with PAE [ 15 , 55 , 56 , 57 ]. Concerns related to selfregulation, such as difficulty soothing or sleep complaints, were also consistent with selfregulatory difficulties seen in this population [ 58 ].…”
Section: Discussionsupporting
confidence: 55%
“…The wide range of mental health challenges documented in the current scoping review (i.e., including suicidal ideation and attempts) supports a more generalized conceptualization of self-regulation impairments than the current Australian Guide. Requiring individuals to meet strict diagnostic criteria for anxiety and depression is likely to limit understanding of the self-regulatory challenges experienced by individuals with FASD (Reid & Petrenko, 2018). Several external and personal factors were identified to be associated with mental health challenges for individuals with FASD.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader sense, deficits in self-regulatory skills in childhood and adolescence, including inhibitory control, are associated with a wide range of negative outcomes during development [50,51,[93][94][95], for example, in poor social, emotional, and cognitive coping [94], poorer physical health and personal finances [93], externalizing problems, substance dependency, and delinquency [50,51,93]. An inhibitory control deficit also appears in other neurodevelopmental disorders, such as autism spectrum disorders and fetal alcohol syndrome, and predicts impairments in executive functioning that may persist throughout development [96][97][98]. Our findings strengthened the results of these previous studies by providing support at the brain activity level, showing that lower levels of early childhood effortful control, especially attentional focusing, could remain persistent throughout development and later be expressed as dysfunctions in the neural mechanism of inhibitory control in adolescence.…”
Section: Discussionmentioning
confidence: 99%